2010
DOI: 10.3174/ajnr.a2105
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of White Matter Tract Damage in Patients with Amyotrophic Lateral Sclerosis: A Diffusion Tensor MR Imaging Tractography Study: Fig 1.

Abstract: BACKGROUND AND PURPOSE:Most DTI studies in ALS have been limited to the assessment of the CST damage. In this study, we used DTI tractography to investigate whether microstructural abnormalities occur in the major motor and extramotor WM tracts in mildly disabled patients with ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
85
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(111 citation statements)
references
References 58 publications
18
85
8
Order By: Relevance
“…8,9 Significant correlations of diffusion parameters with duration, progression, and severity of the disease also have been reported in some previous studies. 2,[9][10][11][12] Even if the clinical signs of ALS consist of motor impairments, recent evidence suggests that ALS is not an isolated motor neuron disorder 13 and that the variability in the location and extension of FA reduction in patients with ALS is such that relying on a priori ROIs to assess DTI changes may not give a consistent and complete picture of ALS neurodegeneration. Therefore, a novel approach based on whole-brain DTI analysis may result in improved accuracy in detecting subclinical microstructural disease-related WM changes.…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…8,9 Significant correlations of diffusion parameters with duration, progression, and severity of the disease also have been reported in some previous studies. 2,[9][10][11][12] Even if the clinical signs of ALS consist of motor impairments, recent evidence suggests that ALS is not an isolated motor neuron disorder 13 and that the variability in the location and extension of FA reduction in patients with ALS is such that relying on a priori ROIs to assess DTI changes may not give a consistent and complete picture of ALS neurodegeneration. Therefore, a novel approach based on whole-brain DTI analysis may result in improved accuracy in detecting subclinical microstructural disease-related WM changes.…”
mentioning
confidence: 67%
“…2 DTI is a relatively new method for structural neuroimaging, which allows visualizing the orientation of the fiber tracts and assessing their integrity in the WM by measuring anisotropic water diffusion properties of the brain with MR imaging. 3 DTI has already produced promising results in assessing UMN pathology in patients with ALS, 2,[4][5][6][7][8][9] suggesting that FA, the most sensitive DTI measure, is reduced along the CSTs due to axonal degeneration and loss of fiber integrity, 2,4-6 though AD, MD, and RD changes along the CSTs and other WM structures may also be indicative of degenerative injury. 8,9 Significant correlations of diffusion parameters with duration, progression, and severity of the disease also have been reported in some previous studies.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported a significant reduction of FA not only in the CST but also in extramotor regions, including the corpus callosum, frontal and parietal WM as well as the hippocampal formation and insula [36,45,48,49]. Using a different methodology, Agosta et al [50] recently reported increased axial diffusivity of the uncinate fasciculus in ALS patients and suggested that uncinate fasciculus involvement may be related to the behavioral symptoms of patients with ALS. The results of these studies support the view that ALS is a multisystem degenerative disease in which abnormalities of extramotor areas play an important role in its pathophysiology.…”
Section: Clinical Applicationmentioning
confidence: 99%